KODIFIKASI LITURGIS PADA RITUAL MAPPADEKKO SEBAGAI RESILENSI BAHASA TORILANGI DI ERA EROSI (KAJIAN SIMIOTIK) - Irna Erviana; Andi Srimularahmah; Andi Muhammad Irfan Taufan Asfar; Muhammad Iqbal Akbar Asfar; Muhammad Idris; Muhammad Asdar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the semiotic signs in the Mappadekko ritual tounderstand how they reflect the sacred values and cultural identity of the BugisBone community. Furthermore, it identifies the process of liturgical codification asa strategy for preserving the Mappadekko ritual and the resilience of the Torilangilanguage amidst modernization. The research also measures the level ofcommunity acceptance towards the adaptation of the Mappadekko tradition in thedigital era. A mixed-method (Sequential Exploratory) design was employed, withdata collected through observation, in-depth interviews, and questionnaires inPationgi Village, Bone Regency. The findings reveal that the Mappadekko ritual isa complex and structured semiotic system where every element functions as ameaningful sign. The Torilangi language, used in prayers and mantras with fixedpronunciation patterns, inherently signifies sacredness and spiritual connection.Liturgical codification, in both oral and practical forms, proves to be an effectivestrategy for maintaining the resilience of the Torilangi language. The community ofPationgi Village shows a high level of acceptance and positive views towardsadapting the Mappadekko tradition in the digital era, particularly for promotion andeducation, while emphasizing the importance of maintaining its sacred essence.